(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
his article gives the highlights of online lessons, the contrasts among online, and offline lessons in showing English as a foreign language. The favorable circumstances and weaknesses of online and offline lessons in instructing English are depicted here. They are considered as current techniques for instructing English including such rules as inspiration, the nature of the view of the material, comprehension of discourse, conquering the language obstruction, and development of the lesson.